2004
DOI: 10.1111/j.1365-2672.2004.02203.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological examination of ready-to-eat cold sliced meats and pate from catering and retail premises in the UK

Abstract: Aims: To establish the microbiological quality of cold ready-to-eat sliced meats and pâté from catering and retail premises, and investigate links hypothesized between foodborne Campylobacter infection and the consumption of cold sliced meats. Methods and Results: A total of 4078 cold meat and pâté samples were collected and examined according to a standardized protocol. Comparison with published microbiological guidelines revealed that most ready-to-eat meat and pâté samples (75%) were of satisfactory/accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 16 publications
(33 reference statements)
2
14
0
Order By: Relevance
“…Products that received heat treatment (deli meat products and pâté) showed a smaller pathogen incidence than smoked products, coinciding with the hypothesis of the greater effectiveness of pasteurization than of smoking in the control of Listeria (Lou & Yousef, 1999). These findings are consistent with the low prevalence detected in vacuum-packed cooked meat and pâté reported in different national and international studies (Uyttendaele, De Troy, & Debevere, 1999;Gombas et al, 2003;Elson, Burgess, Little, & Mitchell, 2004;Wong, CareySmith, Hollis, & Hudson, 2005).…”
Section: Prevalence By Food Category and Type Of Presentationsupporting
confidence: 94%
“…Products that received heat treatment (deli meat products and pâté) showed a smaller pathogen incidence than smoked products, coinciding with the hypothesis of the greater effectiveness of pasteurization than of smoking in the control of Listeria (Lou & Yousef, 1999). These findings are consistent with the low prevalence detected in vacuum-packed cooked meat and pâté reported in different national and international studies (Uyttendaele, De Troy, & Debevere, 1999;Gombas et al, 2003;Elson, Burgess, Little, & Mitchell, 2004;Wong, CareySmith, Hollis, & Hudson, 2005).…”
Section: Prevalence By Food Category and Type Of Presentationsupporting
confidence: 94%
“…However, later cross-contamination during meat processing at plants, at retail or in domestic kitchens may contaminate meat products with Campylobacter spp. (Elson et al 2004;Ghafir et al 2007). Due to the capability of Camp.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, time and temperature were two key issues, research in food production system indicated that time and temperature errors occurred where were of unaccepted microbiological quality (Blakelee & Penner, 1999;Kim & Shanklin, 1999). Elson and his colleagues (Elson, Burqess, Little, & Mitchell, 2004) also reported that poor microbiological quality was associated with storage above 8°C. Secondly, some food additives could also impact of microbial growth.…”
Section: Discussionmentioning
confidence: 97%